Explosive is not a Term Defined in the International System of Units and Should not be Used to Describe Neuromuscular Performance - Bernardo Ide; Amanda Silvatti; Craig Staunton; Moacir Marocolo; Dustin Oranchuk; Gustavo Mota (International Universities Strength and Conditioning Association, 2023)
Despite not being recognized by the International System of Units, explosive is a term often applied in sports science and professional practice. While associated with force, strength, power, performance, exercise, movements, contraction, action, and training, readers may be misled to believe that there are further analyses beyond power output, peak force, contractile rate of force development, and impulse. This critical review discusses the misuse of the term explosive in sports science literature, proposes alternatives, and encourages correct definitions of terms, units, and nomenclature to describe exercise performance. The suggestions provided in this review can help to reduce the confusion and perpetuation of an erroneous understanding of mechanical work, energy, and power in sports science.